Pengaruh Brand Awareness dan Product Quality Terhadap Loyalitas Pelanggan Melalui Keputusan Pembelian Sebagai Variabel Intervening (Studi pada Eastu Coffeebar Wajak) - Usman Fauzi; Nurhidayah Nurhidayah; Abdullah Syakur Novianto (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine the impact of brand awareness and product quality on customer loyalty and purchasing decisions. The population of this study is the visitors of Eastu Coffeebar during one month with a sample size of 100 respondents obtained using non-probability sampling techniques and purposive sampling method. The results showed that brand awareness has no significant impact on customer loyalty, but product quality has a significant impact on customer loyalty. Purchase decision also has a significant impact on customer loyalty. Furthermore, brand awareness and product quality have a significant impact on purchase decision. Both factors also influence customer loyalty through purchase decision. This study used Structural Equation Modeling (SEM) data analysis method assisted by SmartPLS 3.2.9 software. Keyword: Brand Awareness, Product Quality, Loyalty Customer, Purchase Decision